INOVASI PAKAN MANDIRI BERBASIS SUMBER DAYA LOKAL INDIGOFERA SEBAGAI ALTERNATIF BUDIDAYA BERKELANJUTAN IKAN BATAK (Tor soro) - Rumondang, Anne; Huda. J, , Mhd Aidil; Batubara, Helfina Syam (Universitas Mataram, 2025)
The high cost of commercial feed remains the main obstacle in aquaculture, including Batak fish (Tor soro), as it accounts for more than 60% of total production expenses. Dependence on manufactured feed reduces farmers’ independence in managing their aquaculture practices. Meanwhile, Indigofera plants, which are abundant around local communities, contain high protein levels and have strong potential as an alternative feed ingredient. The utilization of Indigofera can serve as an innovative solution to support sustainable aquaculture. This program aims to enhance the independence of Batak fish farmers through the development of Indigofera-based independent feed, thereby reducing production costs and promoting more sustainable farming practices. The activities were implemented through training, demonstrations, and hands-on practice with local farmers. A participatory approach was employed to teach feed formulation, processing, and application of Indigofera-based feed, enabling the community to gain practical skills that can be applied independently. The program resulted in a significant improvement in the knowledge, skills, and self-reliance of Batak fish farmers. Participants were able to understand feed formulation and processing techniques and successfully produced independent feed that could be used sustainably. Economically, production costs were reduced by 25–30% compared to using commercial feed, without compromising the growth performance of Batak fish. In addition, farmers experienced increased motivation, self-confidence, and innovation in developing aquaculture based on local potential. The innovation of Indigofera-based independent feed has proven effective in lowering production costs, improving farmers’ independence, and supporting sustainable Batak fish aquaculture, while simultaneously strengthening local food security, the economic competitiveness of fishing communities, opportunities for business diversification in aquaculture, and encouraging the adoption of simple, environmentally friendly technologies oriented toward community economic independence, with positive impacts on improving collective welfare.